A Vibration-Isolating Blast Technique with Shock-Reflection Device for Dam Foundation Excavation in Complicated Geological Conditions - Haoran Hu; Wenbo Lu; Peng Yan; Ming Chen; Qidong Gao (Shock and Vibration)
Under complicated geological conditions, the vibration in the dam foundation caused by blasting can lead to further deterioration of the foundation rock mass and adversely affect the safety of foundation. In order to effectively control the vibration in dam foundation rock mass, a new bench blasting technique with shock-reflection device is proposed. It introduces a shock-reflection device consisting of high wave impedance block and cushion material, which is placed at the bottom of vertical borehole. This shock-reflection device can effectively reflect the explosion shock wave from vertical direction to horizontal direction after detonation, which can make blasting energy concentrated on the rock mass above dam foundation, so the vibration in the foundation can be controlled. Field blasting experiment was carried out to contrast the blasting induced vibration in foundation rock by bench blasting with shock-reflection device and conventional bench blasting. The results indicate that the vibration in the foundation rock can be reduced by 30%~57%. In addition, the vibration at the bottom of the borehole is also demonstrated by numerical simulation, with results similar to the field experiments. The production experiment results show that the new blasting technique can replace the conventional excavation method of dam foundation in complicated geological conditions, and the new blasting technique has been successfully applied to the Baihetan dam foundation excavation.